PCB Determination in a Contaminated Site: A Comparative Analytical Approach between High- and Low-Resolution GC/MS - Scaglia, Mauro; Bernardello, Marco; Scolari, Sabrina; Rinaldi, Paolo; Cividati, Marika; Volante, Marco (Current Chromatography, 2015)
A study comparing two GC/MS analytical techniques: High Resolution (HRGC/HRMS) and Low Resolution (HRGC/LRMS) Mass Spectrometry was reported on a sample series during an investigation made for assessing PCB contamination levels on a particularly contaminated site. HRGC/HRMS is confirmed to be necessary for a correct quantification especially for Dioxin-like PCBs whereas total PCBs can be determined, with acceptable accuracy, also with HRGC/LRMS. Only few DL-PCB congeners are interfered in HRGC/LRMS mostly due to their low concentration with respect to the other congeners present. Concentrations from 30 to 25000 µg/kg for total PCBs and from 2 to 1800 µg/kg for total Dioxin-like PCBs were found. Levels from 7 to 7000 µg/kg for PCB 209 (decachlorobiphenyl) were found as well. Lo-res/Hi-res response ratios calculated in the three cases ranged from 85% to 155%, from 75 to 195% and from 80% to 160% respectively. The high resolution/low resolution response ratios calculated for each investigated congener were generally close to 1 except for dioxin-like congener where ratios up to 20 were observed.
Keywords: HRCG-HRMS